(3bje GdJYHjQ aj CadGe GdJMQjc h CKQgG GdJQHhj aj GdfMJ GdMQcj (B: s (3OQGSI JLQjHjI (B= Expressive values in animation films and its educational effect upon movement sculpture : An experimental study / s - (3cQje eMeO YHOGdMejO CHhGdbWWs; (3YaGa YHOGdOGje (B: s; (3gGfj eMehO ajUd (B: s ((3GdbGgQI (B: s (3cQje eMeO YHOGdMejO CHhGdbWW (B: s, 2015)
(3bGe GdHGMK HJbSje GdHMK Edj NeS aUhd cj jJecf HYQV GdehVhY HUhQI JJGHYjI dJhVjM CKQ OQGSI CadGe GdJMQjc Ydi Gdbje GdJYHjQjI h GdJQHhjI dOi GdWdGH h LGA GdaUd GdChd (B: " (3jJfGhd GdEWGQ GdYGe ddHMK (B" (3Ke LGA GdaUd GdKGfj (B: " (3GdQShe GdeJMQcI h GdcGQjcGJjQ (B" (3Ke JfGhd GdaUd GdKGdK (B: " (3GdMQcI hCadGe GdJMQjc (B" (3h YQV GdaUd GdQGHY (B: " (3JMdjd deNJGQGJ ef CadGe GdJMQjc (B"(3Ke LGA GdaUd GdNGeS (B: " (3GdEWGQ GdJWHjbj ddHMKs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI GdfhYjI (B- (3bSe GdJQHjI GdafjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJcfhdhLjGs; (3GdNGeGJs; (3Gdaf GdMQcis